Pengaruh senioritas terhadap terjadinya diskriminasi sosial di komunitas remaja dan mahasiswa: upaya pencegahan diskriminasi berbasis senioritas di komunitas remaja dan mahasiswa - Rosyid, Nayla Adiba Nur (Maliki Interdisciplinary Journal, 2026)
The phenomenon of seniority in youth and student communities is part of a social structure that is often considered normal, but has the potential to lead to discriminatory practices. Seniority actually has positive functions, such as providing guidance, transferring experience, and building discipline. However, when taken to extremes and accompanied by a disregard for authority, seniority becomes a source of social inequality. Discrimination based on seniority can manifest through actions such as the right to express opinions, the assignment of disproportionate tasks, intimidation, and social exclusion. This situation not only creates unequal social relationships but also has a serious impact on the mental health of junior members, such as stress, anxiety, insecurity, and decreased self-esteem. This study analyzes the relationship between seniority and social discrimination, while reviewing its impact on psychological dynamics and social welfare in youth and student communities. The results of the study indicate the need for comprehensive prevention efforts, including social literacy, anti-discrimination education, strengthening organizational ethics, and creating an inclusive and democratic environment. In addition, restoring the meaning of seniority as a moral responsibility and role model is an important step in creating healthy social relationships. This study is expected to contribute to the development of strategies for preventing discrimination and forming fair communities that support the psychological development of their members.